2012
DOI: 10.1124/mol.112.081752
|View full text |Cite
|
Sign up to set email alerts
|

Ticlopidine, a Cholestatic Liver Injury-Inducible Drug, Causes Dysfunction of Bile Formation via Diminished Biliary Secretion of Phospholipids: Involvement of Biliary-Excreted Glutathione-Conjugated Ticlopidine Metabolites

Abstract: The antiplatelet drug, ticlopidine (TIC), reportedly causes cholestatic liver injuries. The present study analyzed the effect of TIC on bile formation, revealing that the biliary secretion of phospholipids was significantly decreased in TIC-administered Sprague Dawley (SD) rats. However, the effect of TIC on biliary phospholipids was not observed in SD rats pretreated with diethylaminoethyl diphenylpropylacetate that inhibits cytochrome P450s (P450), or in Eisai hyperbilirubinemic rats (EHBR) lacking functiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…37 A study in rats suggests that adducts are formed following metabolism by cytochrome P450 with evidence for toxicity after biliary excretion of glutathione-conjugated metabolites via MRP2-facilitated transport. 38 In previous studies, 22 Japanese patients with ticlopidine DILI showed an association with an HLA haplotype including A*33:03 (odds ratio 13). 39 In line with current observations, the association was strongest with cholestatic cases with 12 out of 14 cases positive for A*33:03.…”
Section: Discussionmentioning
confidence: 93%
“…37 A study in rats suggests that adducts are formed following metabolism by cytochrome P450 with evidence for toxicity after biliary excretion of glutathione-conjugated metabolites via MRP2-facilitated transport. 38 In previous studies, 22 Japanese patients with ticlopidine DILI showed an association with an HLA haplotype including A*33:03 (odds ratio 13). 39 In line with current observations, the association was strongest with cholestatic cases with 12 out of 14 cases positive for A*33:03.…”
Section: Discussionmentioning
confidence: 93%
“…Ticlopidine-induced cholestatic liver injury is not fully understood, but is often seen in an idiosyncratic manner. In rats, extensive secretion of glutathione conjugates of ticlopidine by MRP2 altered the bile composition and decreased the biliary secretion of phospholipids, which may contribute to the cholestatic hepatotoxicity of ticlopidine 35 . Furthermore, studies point towards a pivotal role of the adaptive immune system, since ticlopidine stimulated T cells of patients with ticlopidine-induced cholestatic hepatitis in vitro , but not T cells from healthy controls 36 .…”
Section: Discussionmentioning
confidence: 99%
“…Forty-eight hours later, cells were collected and the membrane vesicles were isolated by a standard method with repeated centrifugation and homogenization. [10] After the expression of mouse Abcg2 protein was confirmed by western blot analysis, the transport studies of [ 14 C]urate (28 μM, American Radiolabeled Chemicals) were performed by a standard protocol for transport assays with membrane vesicles. [11] All other chemicals used in this study were commercially available and of reagent grade.…”
Section: Methodsmentioning
confidence: 99%